Determinants of access to credit by smallholder farmers in Eastern and Western Kenya - (:unkn) unknown (My University, 2015)
The study sought to first determine the level of access to credit financial services, secondly establish the factors that affect smallholder farmer’s access to credit financial services in Eastern and Western Region and finally the major constraints farmers face in accessing credit financial services in the study areas. Structured interviews were used to collect qualitative and quantitative data from the credit financial service providers in the study area. Baseline survey data from International Maize and Wheat Improvement Centre (CIMMYT) was also used to supplement the collected data. Descriptive and Inferential statistics using the logit model were used to analyze the data. The output from the study indicates that 41.76% and 58.24% of the sampled farming households who accessed credit financial services were from Eastern and Western region respectively. The results from the combined logistic regression indicates that, the marginal effects of education level, occupation and access to extension services were statistically significant with positive effects on access to credit financial services in both Eastern and Western Region. On the other hand, total household annual income and the distance to the credit source were statistically significant with negative influence on access to credit financial services in the two regions. Results from the separate logit regression from the Eastern region indicate that the marginal effects of education level, main occupation, group membership and household income were statistically significant with positive effects on access to credit financial services. In the Western Region on the other hand, the logit results indicate that, the marginal effects of education level, main occupation, and distance to the market and access to extension services were statistically significant with positive effects on access to credit financial services. Level of education and main occupation variables were found to be common and significant in both regions. Group membership was however significant in Eastern region but not significant in the combined regression and in the Western Region. The results also show that, risk associated with borrowing, high interest rates and unavailability of credit financial institutions in the study area as among the major constraints smallholder farmers face. Credit financial providers on the other hand, claim that farming is risky, the distance to the farm makes appraisal process very difficult and stringent regulations in the requirement of collateral as major constraints in providing credit financial services to the smallholder farmers.
A thesis submitted in partial fulfillment of the requirements for the degree of Masters in Business Administration at Strathmore University
The study sought to first determine the level of access to credit financial services, secondly establish the factors that affect smallholder farmer’s access to credit financial services in Eastern and Western Region and finally the major constraints farmers face in accessing credit financial services in the study areas. Structured interviews were used to collect qualitative and quantitative data from the credit financial service providers in the study area. Baseline survey data from International Maize and Wheat Improvement Centre (CIMMYT) was also used to supplement the collected data. Descriptive and Inferential statistics using the logit model were used to analyze the data. The output from the study indicates that 41.76% and 58.24% of the sampled farming households who accessed credit financial services were from Eastern and Western region respectively. The results from the combined logistic regression indicates that, the marginal effects of education level, occupation and access to extension services were statistically significant with positive effects on access to credit financial services in both Eastern and Western Region. On the other hand, total household annual income and the distance to the credit source were statistically significant with negative influence on access to credit financial services in the two regions. Results from the separate logit regression from the Eastern region indicate that the marginal effects of education level, main occupation, group membership and household income were statistically significant with positive effects on access to credit financial services. In the Western Region on the other hand, the logit results indicate that, the marginal effects of education level, main occupation, and distance to the market and access to extension services were statistically significant with positive effects on access to credit financial services. Level of education and main occupation variables were found to be common and significant in both regions. Group membership was however significant in Eastern region but not significant in the combined regression and in the Western Region. The results also show that, risk associated with borrowing, high interest rates and unavailability of credit financial institutions in the study area as among the major constraints smallholder farmers face. Credit financial providers on the other hand, claim that farming is risky, the distance to the farm makes appraisal process very difficult and stringent regulations in the requirement of collateral as major constraints in providing credit financial services to the smallholder farmers.
Keywords: Credit financial services; Credit financial providers; Kenya